Electromyographic validation of the trapezius and serratus anterior muscles in the rowing and frontal-lateral cross, dumbbells exercises - Büll, M. L. [UNESP]; Freitas, V. [UNESP]; Vitti, M. [UNESP]; Rosa, G. J M [UNESP] (My University, 2002)
The trapezius and serratus anterior muscles were studied in four modalities of rowing exercises executed with two grips, middle and closed, in comparison with the four different modalities of frontal-lateral cross, dumbbells exercise. It was used 24 male volunteers, 18 to 25 years old using a 2-channel TECA TE 4 electromyograph and Hewlett Packard surface electrodes. The results showed that TS acted in a higher significant way in all the modalities of rowing than in the supine lateral raise, inclined supine lateral raise and reverse supine lateral raise, dumbbells exercises, and demonstrated no standing frontal-lateral cross, dumbbells. The SI acted more significantly difference among all the execution modalities of rowing and the inclined supine lateral raise, dumbbells exercises than in all the rowing exercises; even though the activity levels do not make us suggest them as an excellent group of exercises for the development of this muscle.
Keywords: adult; arm movement; arm muscle; biomedical technology assessment; controlled study; electrode; electromyogram; electromyography; exercise; hand grip; human; human experiment; male; muscle action potential; muscle development; normal human; sitting; standing; supine position; trapezius muscle; validation process; Adolescent; Adult; Back; Electromyography; Exercise; Humans; Male; Muscle, Skeletal; Posture; Reference Values; Reproducibility of Results; Shoulder; Thorax; Weight Lifting